Regiões metropolitanas paulistas e coordenação intergovernamental: um estudo comparativo - Diba, Ricardo David (2004)
This study portrays the history of the creation of the Metropolitans Regions in São Paulo state, in its formation and trajectory, as well as the construction of its institutions of development. It analyzes the impact of intergovernmental cooperation in the metropolitan management through the participation of the state-level government. The questions that lead this discussion are the impacts of the federative variable and the absence of politics seeking solutions for common problems concerning the various government agencies on a metropolitan region, which discourages intergovernmental cooperation amongst the federative units in these regions. The importance of the intergovernmental coordination is the central point of the analysis. Although coordination and intergovernmental cooperation present technical and political restrictions, they represent and appear to be a solution for collective action problems.